Bridging the Green Gap: Awareness, Attitudes, and Practices of Future Healthcare Leaders in Nepal – A Study for Building an Inclusive and Resilient Health System - Lamichhane, Basu Dev; Koirala, Sharmila; Shahi, Swati Singh; Regmi , Shilpa; Regmi , Pratiksha; Chaudhary, Dhanaraj (NPRC Journal of Multidisciplinary Research, 2025)
Background: The healthcare sector, while dedicated to healing, is a significant contributor to environmental degradation. The concept of "Green Healthcare" aims to resolve this contradiction by promoting sustainable practices that reduce the ecological footprint of healthcare delivery. In Nepal—a nation facing socio-economic disparities, climate vulnerability, and the challenge of building resilient systems—the role of future healthcare leaders is critical. This study investigates the readiness of undergraduate healthcare management (BHCM) students to drive this necessary transition, examining their awareness, attitudes, and practices regarding green healthcare.Objectives: This research aimed to: 1) Assess the level of awareness of green healthcare principles among BHCM students; 2) Evaluate their attitudes towards the role of sustainability in healthcare; and 3) Examine their current engagement in sustainable practices and advocacy. The study sought to identify the gap between knowledge, belief, and action.Methods: A quantitative, cross-sectional study was conducted among 205 undergraduate BHCM students from multiple colleges in Nepal, using a convenience sampling method. Data were collected via a structured online questionnaire with sections on demographics, awareness, attitudes, and practices, using a 5-point Likert scale. Analysis was performed using SPSS, employing descriptive statistics, one-sample t-tests, ANOVA, Pearson’s correlation, and Chi-square tests.Findings: Students demonstrated a significantly high level of theoretical awareness (mean score 3.91/5, p